Charter Schools and the Segregation of Students by Income - Kari Dalane; Dave E. Marcotte (Institute of Labor Economics (IZA), 2021)
The segregation of students by socioeconomic status has been on the rise in American public education between schools during the past several decades. Recent work has demonstrated that segregation is also increasing within schools at the classroom level. In this paper, we contribute to our understanding of the determinants of this increase in socioeconomic segregation within schools. We assess whether growth in the presence and number of nearby charter schools have affected the segregation of socioeconomically disadvantaged students by classroom in traditional public schools (TPS). Using data from North Carolina, we estimate a series of models exploit variation in the number and location of charter schools over time between 2007 and 2014 to estimate the impact of charter school penetration and proximity on levels of within school segregation in TPS classrooms serving grades 3-8. We find that socioeconomic segregation in math and English language arts increase in grades 3-6 when additional charter schools open within large urban districts. We find the largest impacts on schools that are closest to the new charter schools. We estimate that the impact of charter schools can account for almost half of the overall growth in socioeconomic segregation we see over the course of the panel within grades 3-6 in large urban districts.
Keywords: I24; I28; I21; 330; education; charter schools; inequity